Ganges-Brahmaputra-Meghna region : a framework for sustainable development - Ahmad, Qazi Kholiquzzaman, 1943- (Dhaka : University Press Ltd., 2001)
Contributed articles.
A framework for sustainable developement of the GBM region -- GBM regional water vision: Bangladesh perspective / Q.K. Ahmad ... [et al.] -- Making water work to translate poverty into prosperity: the Ganga-Brahmaputra-Barak region / R. Rangachari and B.G. Verghese -- Nepal's water vision and the GBM basin framework / Shanker Krishna Malla ... [et al.].
Includes bibliographical references and index.
Keywords: Sustainable development -- Asia